2017
DOI: 10.1080/24750263.2017.1330429
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical study of the six types of endocrine cells in the enteropancreatic system of the lizard Tropidurus torquatus (Squamata: Tropiduridae)

Abstract: The present study investigates the aspects of endocrine cells secreting cholecystokinin, gastrin, insulin, glucagon, somatostatin and serotonin in the enteropancreatic system of Tropidurus torquatus. The specimens were collected in Marambaia Island, Sepetiba Bay, Rio de Janeiro State, Brazil. The animals' intestine and pancreas were removed, fixed, processed and then subjected to immunohistochemical techniques. Three cell types, immunoreactive (IR) to gastrin, cholecystokinin-8 and serotonin, were identified i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 41 publications
1
10
0
Order By: Relevance
“…The frequency of serotonin-IR cells in the large intestine was moderate compared to the caudal section of the small intestine. These results were similar to the serotonin-IR cells in the small and large intestine of Tropidurus torquatus [18] and in the gastric glands of mammals, including Manis javanica [13]. Serotonin-IR cells were detected in all parts of the digestive tract of Muntiacus muntjak with varied frequency [14].…”
Section: Serotonin-ir Cellssupporting
confidence: 79%
See 4 more Smart Citations
“…The frequency of serotonin-IR cells in the large intestine was moderate compared to the caudal section of the small intestine. These results were similar to the serotonin-IR cells in the small and large intestine of Tropidurus torquatus [18] and in the gastric glands of mammals, including Manis javanica [13]. Serotonin-IR cells were detected in all parts of the digestive tract of Muntiacus muntjak with varied frequency [14].…”
Section: Serotonin-ir Cellssupporting
confidence: 79%
“…A study on the distribution and frequency of endocrine cells in the digestive tract was focused on mammals such us Tragulus javanicus [ 11 ], Bubalus bubalis [ 22 ], Babyrousa babyrussa [ 12 ], Manis javanica [ 13 ], and Muntiacus muntjak [ 14 ]. Several studies that have reported on reptiles focused on small reptiles, including Tropidurus torquatus [ 18 ], Gekko japonicus , Eumeces chinensis , Sphenomorphus indicus , and Eumeces elegans [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations